Higher cardiovascular fitness level is associated with lower cerebrovascular reactivity and perfusion in healthy older adults. Issue 7 (July 2020) - Intzandt, Brittany; Sabra, Dalia; Foster, Catherine; Desjardins-Crépeau, Laurence; Hoge, Richard D; Steele, Christopher J; Bherer, Louis; Gauthier, Claudine J
Aging is accompanied by vascular and structural changes in the brain, which include decreased grey matter volume (GMV), cerebral blood flow (CBF), and cerebrovascular reactivity (CVR). Enhanced fitness in aging has been related to preservation of GMV and CBF, and in some cases CVR, although there are contradictory relationships reported between CVR and fitness. To gain a better understanding of the complex interplay between fitness and GMV, CBF and CVR, the present study assessed these factors concurrently. Data from 50 participants, aged 55 to 72, were used to derive GMV, CBF, CVR and VO2 peak. Results revealed that lower CVR was associated with higher VO2 peak throughout large areas of the cerebral cortex. Within these regions lower fitness was associated with higher CBF and a faster hemodynamic response to hypercapnia. Overall, our results indicate that the relationships between age, fitness, cerebral health and cerebral hemodynamics are complex, likely involving changes in chemosensitivity and autoregulation in addition to changes in arterial stiffness. Future studies should collect other physiological outcomes in parallel with quantitative imaging, such as measures of chemosensitivity and autoregulation, to further understand the intricate effects of fitness on the aging brain, and how this may bias quantitative measures of cerebral health.